The influence of chitosan hydrogels on the morphology of L929 cells - Adrianna Banach-Kopeć; Joanna Pilch; Szymon Mania; Ewa Augustin; Robert Tylingo (Gdańsk University of Technology, 2021)
Representative image at 20x magnification of L929 cells following 24 h of treatment with chitosan derivatives: chitosan dissolved in carbonic acid, chitosan dissolved in carbonic acid endotoxin free, chitosan dissolved in hydroacetic acid at 1:3 diluent factor. The scale bar is 100 µm; Microscope Olympus IX83, Tokyo, Japan).